The effect of intellectual capital disclosure, information asymmetry, and firm size on cost of equity capital with managerial ownership as a moderating variable - Devita Hendini Putri; nur'aini rokhmania (STIE Perbanas Surabaya, 2018)
The purpose of this study is to find out the effect of intellectual capital disclosure, information asymmetry, and firm size on cost of equity capital with managerial ownership as moderating variable. Total sample used in this study is 47 companies listed in the LQ45 Index in Indonesia Stock Exchange (IDX) during the period February 2014 - January 2017. The study period was 2013-2016. Data analysis technique used in this study is descriptive statistical analysis, ordinary least square analysis, and moderated regression analysis. The results of this study show that intellectual capital disclosure has an effect on the cost of equity capital. Components of intellectual capital disclosure, such as human capital, structural capital, and relational capital, have a significant effect on the cost of equity capital. But information asymmetry and firm size have no significant effect on the cost of equity capital. Managerial ownership, as moderating variable, cannot moderate the effect of intellectual capital disclosure, information asymmetry, and firm size on the cost of equity capital.